RECENT ATTAINMENTS IN VIRUS SCIENCE - OSORIO TAFALL, B F (Instituto de Salubridad Publica, CD MEXICO, DF, MEX, 1947)
A bed-side test for the rapid identification of tularemia by serol diagnosis is described The test is performed by mixing a droplet of a concentrated suspension of Pasteurella tularensis with a droplet of whole blood taken from the ear or from the finge
CIENC MEX
Keywords: ATTAINMENTS, VIRUS, SCIENCE; MULTIDISCIPLINARIA; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); VIROLOGIA MEDICA